(untitled) (Revista de Investigaciones Universidad del Quindío, 2017)
Considering the importance of Simulium sp. as a possible vector of Onchocerca volvulus, the parasite that causes oncocercosis, and considering that polytene chromosome analysis has become a powerful tool for identification and classification of vectors or vector populations, a preliminary study was carried out based on the standardization of the extraction technique polytene chromosomes and characterization of these for individuals Simulium sp. found in the Quebrada La Aldana, into Nature Reserve Cedro Rosado, Quindio. The results of the study indicated that the species has n = 3 . The relative length is 125 microns, 46 % corresponds to chromosome I , 33% to chromosome II and chromosome III 21% to total complement . Chromosomes I and II are submetacentric and metacentric III. Chromosomal markers are identified in the tested species and asymmetric index = 0.51.